Peningkatan Hasil Belajar Peserta Didik dengan Menggunakan Aplikasi Wordwall pada Pembelajaran PPKn di SD - Putri, Madani Setia; Sastra, Salsabillah Amalia; Adrias, Adrias; Alwi, Nuuru Azmi (TSAQOFAH, 2024)
This systematic literature review aims to examine the effect of using the WordWall application on student learning outcomes in Civic Education learning in elementary schools. This study was conducted by analyzing relevant research using the Systematic Literature Review (SLR) method. Data were collected from various sources such as scientific journals, seminar proceedings, and research reports. The results of the analysis show that there is strong evidence that the use of the WordWall application can improve student learning outcomes in Civic Education learning in elementary schools.